Performance of an insulated roadway on permafrost, Inuvik, N.W.T. - Johnston, G. H. (1983)
In 1972 four insulated and two uninsulated test sections were installed and instrumented on the Mackenzie Highway (a gravel-surfaced, all-season road) near Inuvik, N.W.T., to evaluate the use of extruded polystyrene board insulation to control permafrost degradation. Two test sections were insulated with a 90-mm layer of insulation, another with a 50-mm layer, and a fourth with 115 mm. Preliminary analysis had indicated that an optimum insulation thickness of about 90 mm would be required. Ground temperature and settlement observations over a 6-year period showed that permafrost aggraded under all insulated test sections, whereas under the uninsulated (control) sections it receded by as much as 60 cm. Approximately 60 cm of settlement was experienced by the control sections, about 30 cm by the 50- mm insulated section, and little or none by the sections having 90 and 115 mm of insulation. The 90 mm of insulation was shown to provide adequate protection against thawing; 50 mm of insulation was not sufficient. En 1972, on a procédé à l'installation d'instruments de mesure sur quatre troncons isolés et deux troncons non isolé s de la route Mackenzie (recouverte de gravier et praticable en toutes saisons) près d'Inuvik, (T. du N.-O.), afin d'évaluer l'efficacité d'une couche de panneaux isolants en polystyrène extrudé destinés à éviter la dégradation de la chaussée due au pergélisol. Deux troncons d'essai ont été dotés d'une couche de 90 mm d'isolant, le troisième d'une couche de 50 mm et le quatrième d'une couche de 115 mm. Une étude préliminaire avait indiqué que l'épaisseur optimale d'isolant requise était d'environ 90 mm. L'observation des températures et du tassement du sol sur une période de six ans a indiqué une élévation du pergélisol sous tous les troncons isolés, tandis que sous les troncons non isolés il s'est enfoncé, parfois même de 60 cm. On a observé un tassement d'environ 60 cm pour les troncons témoins, d'environ 30 cm pour les troncons ayant 50 mm d'isolant et aucun tassement ou presque pour les ...